Global topics and novel approaches in the study of air pollution, climate change and forest ecosystems. (June 2016) - Sicard, Pierre; Augustaitis, Algirdas; Belyazid, Salim; Calfapietra, Carlo; de Marco, Alessandra; Fenn, Mark; Bytnerowicz, Andrzej; Grulke, Nancy; He, Shang; Matyssek, Rainer; Serengil, Yusuf; Wieser, Gerhard; et al.
Abstract: Research directions from the 27th conference for Specialists in Air Pollution and Climate Change Effects on Forest Ecosystems (2015) reflect knowledge advancements about (i) Mechanistic bases of tree responses to multiple climate and pollution stressors, in particular the interaction of ozone (O3 ) with nitrogen (N) deposition and drought; (ii) Linking genetic control with physiological whole-tree activity; (iii) Epigenetic responses to climate change and air pollution; (iv) Embedding individual tree performance into the multi-factorial stand-level interaction network; (v) Interactions of biogenic and anthropogenic volatile compounds (molecular, functional and ecological bases); (vi) Estimating the potential for carbon/pollution mitigation and cost effectiveness of urban and peri-urban forests; (vii) Selection of trees adapted to the urban environment; (viii) Trophic, competitive and host/parasite relationships under changing pollution and climate; (ix) Atmosphere–biosphere–pedosphere interactions as affected by anthropospheric changes; (x) Statistical analyses for epidemiological investigations; (xi) Use of monitoring for the validation of models; (xii) Holistic view for linking the climate, carbon, N and O3 modelling; (xiii) Inclusion of multiple environmental stresses (biotic and abiotic) in critical load determinations; (xiv) Ecological impacts of N deposition in the under-investigated areas; (xv) Empirical models for mechanistic effects at the local scale; (xvi) Broad-scale N and sulphur deposition input and their effects on forest ecosystem services; (xvii) Measurements of dry deposition of N; (xviii) Assessment of evapotranspiration; (xix) Remote sensing assessment of hydrological parameters; and (xx) Forest management for maximizing water provision and overall forest ecosystem services. Ground-level O3 is still the phytotoxic air pollutant of major concern to forest health. Specific issues about O3 are: (xxi) Developing dose–response relationships and stomatal O3 flux parameterizations for risk assessment, especially, in under-investigated regions; (xxii) Defining biologically based O3 standards for protection thresholds and critical levels; (xxiii) Use of free-air exposure facilities; (xxiv) Assessing O3 impacts on forest ecosystem services. Highlights: Research directions from the biennial IUFRO RG conference. Focus on ozone, nitrogen deposition and climate change. Linking genetic control with physiological activity recommended. Multi-factorial stand-level investigations recommended. Bridging research, monitoring and modelling recommended. Abstract : Multi-factorial studies are a key to investigate the complex interactions between climate, pollution and forests (from genes to the planet).